A novel shape-stabilized phase change material with tunable thermal conductivity for cold chain applications - Dixit, Prakhar (2024)
Phase change materials (PCMs) are popular in cold-chain logistics as evidenced by the commercial success of various PCM-based thermal shippers. Improvement in the thermal performance of PCMs can improve their sustainability and viability. Herein, a novel, thermally conductive PCM composite is evaluated for transporting thermally sensitive perishables in the temperature window of −14 °C to 25 °C. The PCM (OH-64), developed from a eutectic mixture of a commercial PCM and hexadecane, was found to have a melting temperature of 6.87 °C and crystallization onset at 4.86 °C. Expanded graphite (EG) was added to improve the shape stability and reduce the activation time. The thermal characterization of OH-64 indicated no significant changes in the melting/crystallization temperature after the addition of 11.1 wt% EG and resulted in only a 5% decrease in fusion enthalpy as compared to the original blend. The composite's thermal conductivity dependence on the bulk density suggests that this property may be tuned by changing the morphology of the resulting composites. The applicability of OH-64 was evaluated by incorporating it into a thermal shipper with a chocolate payload and subjecting the box to different ambient temperatures. The thermal buffering effect of the composite was significant despite the absence of thermal insulation. Thus, the OH-64 eutectic PCM composite prepared in this study would be potentially useful for low-temperature thermal buffering applications in cold-chain food and pharmaceutical logistics.